The Sentimental Eloquence of the Black American Scholar: Ellison’s Invisible “Man Thinking” and Feeling - Silke Schmidt (Current Objectives of Postgraduate American Studies)
Grief is one of the most powerful sentiments depicted in literary works throughout human history. In the cultural history of the U.S., the open expression of grief by means of public mourning mostly stands in the African American tradition. One of the most outstanding African American literary figures of the twentieth century is Ralph Ellison. His Invisible Man“ (1952) represents an epitome of modern sentimentalism when it comes to the political project of mourning America. Despite the wide attention dedicated to the work, critics have paid scarce attention to Ellison’s close ties to nineteenth-century sentimentalism. This especially applies to the author’s ambivalent relation to Ralph Waldo Emerson and his vision of the “American Scholar.“ The present article analyzes the complex employment of Emersonian thought “revised à la Ellison“ (Lee 336) in a contextual reading which regards Invisible Man and its sentimental function within the larger network of literary, social, and political discourse. It argues that Ellison’s Invisible Man“ reflects Emerson’s American Scholar as “Man Thinking“ and feeling. The mourning of a free and equal America thus turns out to be a powerful element of the  sentimental mode. The close-reading analysis shows in how far both authors can be read to be writing in the sentimental tradition which, in contrast to many critics' opinions, has not lost its appeal but continues to echo in the language of contemporary political figures such as Obama.